1st Global Conference on Biomedical Engineering & 9th Asian-Pacific Conference on Medical and Biological Engineering : October 9-12, 2014, Tainan, Taiwan - Su, Fong-Chin; Wang, Shyh-Hau; Yeh, Ming-Long (IFMBE Proceedings,, 2015)
This volume presents the proceedings of the 9th Asian-Pacific Conference on Medical and Biological Engineering (APCMBE 2014). The proceedings address a broad spectrum of topics from Bioengineering and Biomedicine, like Biomaterials, Artificial Organs, Tissue Engineering, Nanobiotechnology and Nanomedicine, Biomedical Imaging, Bio MEMS, Biosignal Processing, Digital Medicine, BME Education. It helps medical and biological engineering professionals to interact and exchange their ideas and experiences.